Inserção urbana : uma análise de empreendimentos do programa MCMV em Cuiabá - Evangelista, Fabrina Inez da Conceição (2018)
The housing deficit and the need to leverage the country's economy led, in 2009, to the creation of a new national housing policy, the Minha Casa Minha Vida (MCMV). This program establishes minimum conditions for the elaboration of projects, as well as the specific form of attendance by income range, both for people living in the city and for those who live in the countryside. In its current phase, denominated MCMV 3, it is perceived more concern with the sustainability of the housing developments. Given this scenario and based on several academic studies that address the same theme in other regions of the country, this study presents an analysis, on a local scale, of the urban quality of low income housing MCMV developments located in the city of Cuiabá (state of Mato Grosso), from the perspective of urban insertion. Among the main aspects considered in the research are: urban mesh morphology, transport infrastructure; and availability of areas of common use, public service equipment and trade. These items were evaluated based on indicators present in one of the methodological tools gathered in this work. The main impressions obtained at the end of this study were: i. The basic assumptions of urban quality, from the point of view of the sustainability of housing projects, which are: areas within the urban network equipped with infrastructure and with the presence of basic services necessary for its implementation, were not fully respected; and, ii. The cases analyzed do not present, in full, minimum standards of urban design, such as: mobility and accessibility, functional diversity and free spaces.